The production efficiency of intercropping systems annual and perennial crops in southern Ethiopia: a comparison of distance functions and production frontiers - Alene, A.; Manyong, Victor M.; Gockowski, J. (Elsevier, 2006)
This study measures the efficiency of intercropping systems of annual and perennial crops production in southern Ethiopia using the stochastic frontier production function (SFP), parametric distance functions (PDF), and data envelopment analysis (DEA), and compares the empirical performances of the three methods. The results from the multi-output PDF and DEA approaches have revealed significantly higher efficiency of the systems than the single-output SFP approach. We find that both DEA and PDF are appropriate in multi-output agriculture involving intercropping of annual and perennial crops. Single-output measures of productivity and efficiency may thus underestimate resource use efficiency of intercropping systems. Based on the geometric mean technical efficiency predictions for each data point using the preferred PDF and DEA approaches, the sample farmers in southern Ethiopia have an average technical efficiency of 91%. The results confirm farmers’ efficient use of land and other resources through innovative cropping systems. Technologies that are appropriate to such systems may thus be needed for greater intensification.